Collagen peptides administration in early enteral nutrition intervention attenuates burn-induced intestinal barrier disruption: Effects on tight junction structure. (April 2019) - Chen, Qianru; Gao, Xiang; Zhang, Hongwei; Li, Bafang; Yu, Guangli; Li, Bo
Graphical abstract: Highlights: Collagen peptides revealed protective effects on intestinal barrier function in burned mice. Collagen peptides ameliorated burn-induced collapse of tight junction structure. Collagen peptides diminished burn-induced increase of MLCK expression and MLC phosphorylation. Collagen peptides inhibited burn-induced activation of NFκB and MAPK pathways. Abstract: The effect of collagen peptides (CPs) administration in early basic enteral nutrition (EN) intervention after burn injury on intestinal barrier function was investigated in mice model. Burn-induced increases of intestinal permeability and disruption of intestinal barrier integrity were significantly attenuated by CPs supplemented EN at post-burn day 1, 3 and 7 as compared with only basic EN fed group. CPs revealed a prominent amelioration of the expression and localization of tight junction protein ZO-1 and occludin in intestinal mucosa. Furthermore, CPs administration significantly inhibited burn-induced elevation of MLCK expression and MLC phosphorylation. Simultaneously, the activation of involved signal pathways, such as NF-κB p65, MAPK p38, ERK and JNK were diminished in different extent by CPs addition. Therefore, CPs could be considered as a beneficial adjunct in early EN intervention to prevent intestinal barrier disruption following burn injury, because of its protective effects on intestinal tight junction integrity.